Prognostic and Immune Implications of a Novel Pyroptosis-Related Five-Gene Signature in Breast Cancer - Zheng, Yuanyuan; Wang, Kainan; Li, Ning; Zhang, Qianran; Chen, Fengxi; Li, Man (Frontiers in Surgery, 2022)
Background: Breast cancer (BC) is the most usual malignancy in global women and shows enormous heterogeneity. Pyroptosis plays a considerable role in tumor occurrence and growth. Nevertheless, the potential correlativity between pyroptosis-related genes (PRGs) and BC immune microenvironment remains to be explored. Materials and methods: 38 PRGs were notably differentially expressed between BC and non-cancerous breast samples from the TCGA-BRCA cohort. Consensus clustering by the 38 PRGs classified 1089 patients into two pyroptosis-related (PR) patterns. On the basis of the differentially expressed genes (DEGs) between two clusters, a PR five-gene prognostic signature was built by applying univariate- and LASSO-Cox analyses. ESTIMATE, CIBERSORT, and ssGSEA were utilized to explore the BC tumor microenvironment (TME). Results: The two PR clusters had diverse clinicopathological traits, survival outcomes and immunocyte infiltration features in TME. The constructed five-signature model (SEMA3B, IGKC, KLRB1, BIRC3, PSME2) stratified BC patients into two risk subgroups according to the calculated median risk score. Patients in low scoring subgroup had better survival possibilities and more abundant immunocyte infiltration. Similar conclusions can be obtained from an external validation set. Conclusions: Our findings indicate that the PRGs have notable influence on BC immune microenvironment. The PR clusters and related prognostic signature provide support for further studies targeting pyroptosis to optimize treatment measures of BC patients and their responses to immune therapy.